Unsteady MHD mixed convection stagnation-point flow in a micropolar fluid on a vertical surface in a porous medium with soret and dufour effects - Aurangzaib, Aurangzaib; Kasim, A. R. M.; Mohammad, Nurul Farahain; Shafie, Sharidan (Begell House, Inc., 2013)
The problem of an unsteady MHD mixed convection flow with heat and mass transfer in a micropolar fluid near the forward stagnation point in a porous medium with Soret and Dufour effects has been investigated. The self‐similarity transformation is used to transform the governing equations and then to solve them numerically using an implicit finite difference scheme. In this study, we consider both assisting and opposing flows. The profiles of velocity, microrotation, temperature, and concentration, as well as the skin friction, and the rate of heat and mass transfer are determined and presented graphically for physical parameters. The results show that the magnetic parameter decreases the reduced skin friction and reduced heat and mass transfer for the assisting flow while the opposite trend is observed for the case of opposing flow. It is also found that the buoyancy parameter decreases the thermal and concentration boundary layer thickness for an assisting flow and increases for an opposing one.